The additive effects of atorvastatin and insulin on renal function and renal organic anion transporter 3 function in diabetic rats - Laongdao Thongnak (2018)
© 2017 The Author(s). Hyperglycemia-induced oxidative stress is usually found in diabetic condition. 3-hydroxy-3-methylglutaryl coenzyme-A (HMG-CoA) reductase inhibitors, statins, are widely used as cholesterol-lowering medication with several "pleiotropic" effects in diabetic patients. This study aims to evaluate whether the protective effects of atorvastatin and insulin on renal function and renal organic anion transporter 3 (Oat3) function involve the modulation of oxidative stress and pancreatic function in type 1 diabetic rats. Type 1 diabetes was induced by intraperitoneal injection of streptozotocin (50 mg/kg BW). Atorvastatin and insulin as single or combined treatment were given for 4 weeks after diabetic condition had been confirmed. Diabetic rats demonstrated renal function and renal Oat3 function impairment with an increased MDA level and decreased SOD protein expression concomitant with stimulation of renal Nrf2 and HO-1 protein expression. Insulin plus atorvastatin (combined) treatment effectively restored renal function as well as renal Oat3 function which correlated with the decrease in hyperglycemia and oxidative stress. Moreover, pancreatic inflammation and apoptosis in diabetic rats were ameliorated by the combined drugs treatment. Therefore, atorvastatin plus insulin seems to exert the additive effect in improving renal functionby alleviating hyperglycemiaand the modulation of oxidative stress, inflammation and apoptosis.